8821/2 amazing answers to your questions about the Titanic (Canada : Madison Press Book, 1998)
1. Titanic (Steamship)--Miscellanea--Juvenile literature. 2. Shipwrecks--North Atlantic Ocean--Miscellanea--Juvenile literature.
Basic ed. students